1986
DOI: 10.1111/j.1755-3768.1986.tb06895.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of sodium hyaluronate (Healon) in the treatment of complicated cases of retinal detachment

Abstract: Thirty-six eyes with retinal detachment and various degrees of proliferative vitreoretinopathy were operated with conventional buckling techniques and the additional use of intravitreal injected sodium hyaluronate (Healon). Eighteen eyes (50%) had re-attached retina 6 months post-operatively. The re-attachment rate depended upon the severity of the proliferative vitreoretinopathy. Three of 4 eyes with grade B, 4 of 5 with grade C-1, 8 of 13 with grade C-2, 2 of 11 with grade C-3 and 1 of 3 eyes with grade D-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For much larger volumes of OVD, IOP rises have been observed only after OVD injection into the posterior segment for retinal detachment surgery. 13 Intraocular pressure-lowering medication may be applied once at the end of cataract surgery to lower IOP in the first postoperative hours. 12 The same fixed dorzolamide-timolol combination used in the present study has been shown to be effective in reducing IOP 6 hours and 20 to 24 hours after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For much larger volumes of OVD, IOP rises have been observed only after OVD injection into the posterior segment for retinal detachment surgery. 13 Intraocular pressure-lowering medication may be applied once at the end of cataract surgery to lower IOP in the first postoperative hours. 12 The same fixed dorzolamide-timolol combination used in the present study has been shown to be effective in reducing IOP 6 hours and 20 to 24 hours after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The use of derivates of sodium hyaluronic acid in vitreoretinal surgery predates their ubiquitous use in cataract and anterior segment surgery [12,14,[40][41][42], but their use in a clinical setting has been limited mainly due to concern about short term side effects and retention time [41,43]. Healaflow® is a commercially available compound consisting of a cross-linked sodium hyaluronic acid hydrogel and is FDA approved for use in glaucoma surgery [22,23].…”
Section: Our Previous Results and Our Hypothesismentioning
confidence: 99%